PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL PADA DIREKTORAT JENDERAL PERBENDAHARAAN - Latif Farid Muharrom; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to investigated the effect of budgeting participation or managerial performance in organization of public sector. This research also testing if organization commitment and innovation perception variables facilitate relationship between budgeting participation and managerial performance. Data collecting was done by researcher through survey to organization of public sector, Directorate General of Treasury, Ministry of Finance. Questionnaires were given to 207 echelons IV in Directorate General of Treasury, 113 (54,59%) among them were filled completely and used for this research. This research used Path Analysis with IBM SPSS v20 to process data. The result of this research shows that there are direct influence of budgeting participation to managerial performance. Budgeting participation also significantly influent to organization performance and innovation perception. However, budgeting participation does not has significantly indirect influence to managerial performance through intervening of organization commitment and innovation perception.